CAG Expansion in Androgen Receptor Gene of Infertile Men in Erbil Governorate - Dashne Abdulla Salih; Karim Jalal Karim (Kurdistan Journal of Applied Research)
Spermatogenesis and male phenotypic development during puberty are mainly done by androgen and their function is regulated by the androgen receptor (AR) gene. This gene has a polymorphism site in Exon1 which encode androgen receptor and have various length of CAG trinucleotide repeat which causes the production of polyglutamine chain in different length of the N-terminal domain of AR protein which reduces producing sperm by disrupting spermatogenesis.